Research on welding deformation for box girder of bridge crane based on thermal elasto-plastic theory. (May 2018) - Tong, Yifei; Ge, Zhihao; Zhuo, Xingcheng; Shen, Guomin; Li, Dongbo; Li, Xiangdong
Cranes are mechanical devices widely used to hoist materials in engineering. The box girder of a bridge crane is formed by welding. During welding, residual stress and welding deformation will be inevitably generated due to the instantaneous hot temperature, which will affect not only the camber of the crane but also the operational performance of the traveling trolleys. Therefore, understanding the laws governing the welding deformation can lead to better control of camber cutting of the crane web to avoid unnecessary corrections, reasonably control the geometry shape of the girder and ensure the good operational performances of the trolleys. To achieve this goal, thermal elasto-plastic analysis method together with the Abaqus software is used to analyze the welding from the upper and lower covers to the web, from the upper and lower steel angles to the web, and from the web to the ribs. For the welding simulations, Gaussian movable heat sources, with the advantages of low computational cost, fast calculation speed, easy convergence, and a reasonable number of segments, are selected. The simulation results are compared with the experimental results to verify the reliability, accuracy, and efficiency of the numerical welding model. Finally, the simulation results are discussed, and design guidance for the web is proposed.